2006
DOI: 10.1007/s10620-006-3137-8
|View full text |Cite
|
Sign up to set email alerts
|

Improved Prognosis of Cirrhosis Patients with Esophageal Varices and Thrombocytopenia Treated by Endoscopic Variceal Ligation Plus Partial Splenic Embolization

Abstract: The aim of this study was to assess the efficacy of the combination of endoscopic variceal ligation (EVL) and partial splenic embolization (PSE) compared with EVL alone in cirrhosis patients with thrombocytopenia. In a prospective study, 84 cirrhosis patients with esophageal varices and thrombocytopenia (platelet count < 50,000/mm(3)) underwent EVL plus PSE (N = 42) or EVL alone (N = 42). Primary end points assessed during the follow-up period included the recurrence of varices, progression to variceal bleedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…The rate of severe complications after PSE for hypersplenism has been shown to range between 0 and 16 per cent 6,11,15,18 . Some studies have reported that PSE for hypersplenism is associated with no deaths 4,11,15 , whereas others have reported a mortality rate ranging from 5·9 to 12 per cent 6,18,20 . Recently, laparoscopic splenectomy has been performed for hypersplenisminduced thrombocytopenia in patients with cirrhosis, although only in those with Child class A and B disease 21 -23 .…”
Section: Discussionmentioning
confidence: 99%
“…The rate of severe complications after PSE for hypersplenism has been shown to range between 0 and 16 per cent 6,11,15,18 . Some studies have reported that PSE for hypersplenism is associated with no deaths 4,11,15 , whereas others have reported a mortality rate ranging from 5·9 to 12 per cent 6,18,20 . Recently, laparoscopic splenectomy has been performed for hypersplenisminduced thrombocytopenia in patients with cirrhosis, although only in those with Child class A and B disease 21 -23 .…”
Section: Discussionmentioning
confidence: 99%
“…Ohmoto conducted a study of 84 cirrhotic patients with large esophageal varices and thrombocytopenia [33] . 42 patients were treated with endoscopic variceal ligation (EVL) and 42 were treated with EVL and PSE.…”
Section: Hematologic Indicesmentioning
confidence: 99%
“…All of the above agents are typically delivered via a suspension containing contrast and, frequently, antibiotics. Of the studies reviewed, 14 noted the material used in embolization [9,[12][13][14][15][16][17][18]33,[44][45][46][47][48] . 8 of 14 used gel foam, 2 used tris-acryl gelatin microspheres, 2 used PVA particles, 1 used gelfoam and PVA particles in separate cohorts, and 1 used a combination of tris-acryl gelatin microspheres and PVA.…”
Section: Techniquementioning
confidence: 99%
“…Ohmoto et al [1] provide data that might compel one to utilize partial splenic embolization (PSE) in conjunction with endoscopic variceal ligation (EVL) to treat esophageal varices in patients who are not liver transplant candidates. The authors found that this treatment strategy prevented the recurrence of varices and progression to variceal bleeding and decreased mortality from variceal bleeding when compared with EVL alone.…”
Section: To the Editormentioning
confidence: 99%